Structure-specificity relationships for haloalkane dehalogenases - Damborský, J; Rorije, E; Jesenská, A; Nagata, Y; Klopman, G; Peijnenburg, W J (Environmental toxicology and chemistry, 2001)
A structural analysis of the substrate specificity of hydrolytic dehalogenases originating from three different bacterial isolates has been performed using the multiple computer-automated structure evaluation methodology. This methodology identifies structural fragments in substrate molecules that either activate or deactivate biological processes. The analysis presented in this contribution is based on newly measured dehalogenation data combined with data from the literature (91 substrates). The enzymes under study represent different specificity classes of haloalkane dehalogenases (haloalkane dehalogenase from Xanthobacter autotrophicus GJ10, Rhodococcus erythropolis Y2, and Sphingomonas paucimobilis UT26). Three sets of structural rules have been identified to explain their substrate specificity and to predict activity for untested substrates. Predictions of activity and inactivity based on the structural rules from this analysis were provided for those compounds that were not yet tested experimentally. Predictions were also made for the compounds with available experimental data not used for the model construction (i.e., the external validation set). Correct predictions were obtained for 28 of 30 compounds in the validation set. Incorrect predictions were noted for two substrates outside the chemical domain of the set of compounds for which the structural rules were generated. A mechanistic interpretation of the structural rules generated provided a fundamental understanding of the structure-specificity relationships for the family of haloalkane dehalogenases.
Keywords: Biodegradation, Environmental; Structure-Activity Relationship; látky znečišťující životní prostředí; teoretické modely; předpověď; Hydrolases; Sphingomonas; Forecasting; referenční hodnoty; hydrolasy; vztahy mezi strukturou a aktivitou; Rhodococcus; Models, Theoretical; Reference Values; halogeny; Halogens; Environmental Pollutants; Xanthobacter; biodegradace